Use of immune checkpoint inhibitors in solid organ transplant recipients with advanced cutaneous malignancies - Ji, Stephanie; Liu, Hao; Pachella, Laura; Stephenson, Ryan D.; Groisberg, Roman; Weiss, Sarah A. (Frontiers in Transplantation, 2023)
Background: Immune checkpoint inhibitors (ICI) are standard of care therapy for patients with cutaneous malignancies, the most frequently diagnosed cancers in solid organ transplant (SOT) recipients. The activity and rate of allograft rejection in SOT recipients with advanced skin cancers treated with ICI is understudied. Methods: We conducted a retrospective analysis of SOT recipients with advanced melanoma, cutaneous squamous cell carcinoma (cSCC), and merkel cell carcinoma (MCC) who were treated with ICI. Unpublished cases from our institution and published cases from the literature were aggregated. Demographics, type of immunosuppressive therapy, type of ICI(s) administered, prior systemic therapies, tumor response to ICI, and evidence of organ rejection and/or failure were recorded. Objective response rates (ORR) and rates of graft rejection and failure are reported. Results: Ninety patients were identified; four patients from our institution and 86 unique patients from a literature review. ORR to first-line ICI for the entire cohort was 41.1% (37/90). ORR by tumor type was 31% (18/58), 64.3% (18/28), and 25.0% (1/4) for melanoma, cSCC, and MCC, respectively. The rate of graft rejection was 37.8% (34/90) with 61.8% (21/34) of these cases progressing to graft failure. Number of immunosuppressive agents (0, 1, 2, or 3) was inversely associated with rate of graft failure. Conclusions: In this retrospective analysis, ICIs demonstrate clinical activity in SOT recipients with cutaneous malignancies; however, the rate of graft rejection is high. Treatment plans should be individualized through thorough interdisciplinary discussion. Immunosuppressive modifications may be considered prior to starting treatment, but when feasible, enrollment on clinical trials is preferred.